Hierarchically Porous Carbon Nanofibers with Controllable Porosity Derived from Iodinated Polyvinyl Alcohol for Supercapacitors. Issue 16 (17th June 2020) - Seok, Jae Young; Song, Seung A; Yang, Inyeong; Woo, Kyoohee; Park, Seong Yeon; Park, Jung Hwan; Kim, Sanha; Kim, Seong Su; Yang, Minyang
Abstract: Porous carbon nanoframeworks have attracted considerable interest for promising applications such as water purification, catalyst supports, gas adsorption, and energy storage owing to their high surface area and electrical conductivity. Traditional synthetic methods applied for porous carbon commonly involve a number of toxic organic solvents and post‐treatments, which are time‐consuming and energy inefficient. Herein, the authors report a facile synthetic method for generating atomically small pores in carbon nanofibers, with sizes varying from ≈0.55 nm to a few nanometers, using water‐soluble and cost‐effective polyvinyl alcohol (PVA) nanofibers as a precursor through the introduction of an iodine treatment. In particular, the generation mechanism of ultrafine pores during the carbonization of iodinated PVA are deeply analyzed and elucidated through meticulous investigations into their chemical/structural properties. By the suggested mechanism, the specific surface area of the generated pores is found to be extensively controlled from 100–650 m 2 g −1 . This phenomenon is advanced to produce well‐controlled hierarchically porous carbon nanofibers, and analyzes the corresponding electrochemical characteristics to explore the potential usage of such fibers as a supercapacitor. Abstract : Hierarchically porous carbon nanofibers (HPCNFs) derived from polyvinyl alcohol nanofibers are prepared using a single high‐temperature process through an iodine treatment. The corresponding mechanism of pore generation is deeply investigated, enabling control of the specific surface area of the HPCNFs with an extensive range of 100–650 m 2 g −1 . This HPCNF demonstrates a high capacitance, and exceptional stability as a supercapacitor.